2015
DOI: 10.1177/0042098015571887
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid spatialities: Multi-storey extensions of socialist blocks of flats under post-socialist transition in Serbia, the case of Nis

Abstract: The aim of this research is to study the emergence and evolution of the multi-storey extension (MSE) of socialist blocks of flats in the form of additional storeys or lofts on top of host buildings, which is seen as a dominant model of post-socialist spatial change in inherited multi-storey housing areas in Serbia. Relying on an analysis of empirical data sources, interviews, observation and a comparative analysis, the paper investigates the MSE as a predominantly self-organising process. It also considers its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…It appears that tenants have deliberately traded-off partial approbation of public space and distortion of buildings for better proximity to the needed services. Considering what Vranic, Vasilevska and Haas (2015) observed, GC emerged in line with a boom in multi-story extensions of existing buildings in the analyzed area, which violated the quality of public space; thus, detrition of public space can't be exclusively attached to GC. Certainly, GC is a quality that has contributed the livability of neighborhoods.…”
Section: Resultsmentioning
confidence: 89%
“…It appears that tenants have deliberately traded-off partial approbation of public space and distortion of buildings for better proximity to the needed services. Considering what Vranic, Vasilevska and Haas (2015) observed, GC emerged in line with a boom in multi-story extensions of existing buildings in the analyzed area, which violated the quality of public space; thus, detrition of public space can't be exclusively attached to GC. Certainly, GC is a quality that has contributed the livability of neighborhoods.…”
Section: Resultsmentioning
confidence: 89%
“…Previous research was mainly focused on urban and housing policies and their spatial, economic and social implications at the national level (Petrovic, 2001; Nedovic-Budic, 2012); on the capital city Belgrade (Hirt, 2009), or on the second-tier cities (Vasilevska et al, 2014;Vasilevska et al, 2015;Vranic et al, 2016). Although these studies have identified TTs in the LHEs at general level, the academic and empirical research on their presence, pace and intensity in different city size categories were neglected in Serbia's post-socialist discourse.…”
Section: Within This Mode Decrease Of Public Open Space and Degradatmentioning
confidence: 99%
“…For instance, Lux and Sunega (2014, 514) proposed -in a quite critical-realist vein -an explanation of path dependence framed under the "privatization trap" as "a trickle down mechanism" generating expectations of continued privatization in the newly built social housing and reinforcing already strong social norms of owner-occupation. Likewise, in-kind restitution of housing and land, and housing privatization have resulted in fragmented property rights with long-term consequences for how housing is developed and maintained (Górczyńska 2017;Lux, Cirman, and Sunega 2017;Soaita 2012;Vranic, Vasilevska, and Haas 2015). We anchor the idea of path-dependent change in the communist past by highlighting key differences across the political economies and forms of housing provisions across the communist states in the following section.…”
Section: The Ontological Depth Of Housing Quality: a Critical-realistmentioning
confidence: 99%
“…As the 1990s reforms of housing privatization and restitution are by now well-documented (Clapham et al 1996;Lowe and Tsenkova 2003), we will focus on the changes that have taken place since 2000. Economic growth and remittances have stimulated new housing construction throughout the region, stirring (self-built) suburbanization (Hirt 2008;Soaita 2013;Stanilov 2007), private regeneration of communist housing estates (Cirman, Mandič, and Zorić 2013;Soaita 2012;Vranic, Vasilevska, and Haas 2015) and gentrification in some cities (Górczyńska 2016;Kovács, Wiessner, and Zischner 2012).…”
Section: Mapping Post-communist Structural Changementioning
confidence: 99%